2013
DOI: 10.1016/j.vaccine.2013.06.037
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of pneumococcal conjugate vaccination in immunocompromised adults

Abstract: Objective Pneumococcal disease is a significant problem in immunocompromised persons, particularly in HIV-infected individuals. The CDC recently updated pneumococcal vaccination recommendations for immunocompromised adults, adding the 13-valent pneumococcal conjugate vaccine (PCV13) to the previously recommended 23-valent pneumococcal polysaccharide vaccine (PPSV23). This analysis estimates the cost-effectiveness of pneumococcal vaccination strategies in HIV-infected individuals and in the broader immunocompro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 29 publications
0
41
1
3
Order By: Relevance
“…[24][25][26][27][28] two were conducted for Italy 29,30 and the remaining 3 were performed for England, the Netherlands and Spain respectively. [31][32][33] Of the 5 US publications, 3 were authored by Smith et al 24,26,27 with 2 others by Weycker et al and…”
Section: Setting and Intervention Evaluatedmentioning
confidence: 99%
See 3 more Smart Citations
“…[24][25][26][27][28] two were conducted for Italy 29,30 and the remaining 3 were performed for England, the Netherlands and Spain respectively. [31][32][33] Of the 5 US publications, 3 were authored by Smith et al 24,26,27 with 2 others by Weycker et al and…”
Section: Setting and Intervention Evaluatedmentioning
confidence: 99%
“…39 In terms of the type of economic evaluation, 7 publications were cost-utility analyses, presenting cost per Quality Adjusted Life Year (QALY) gained as the primary outcome. 24,[26][27][28][29]31,32 Whereas the studies by Liguori et al 30 and Pradas et al 33 could be classified as cost-effectiveness analyses, calculating the cost per case of pneumococcal disease avoided as the main outcome. …”
Section: Economic Evaluation Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…25,52 Modelling studies of PCV13 in older adults, including immunocompromised adults, have suggested that a single dose of PCV13 may be more practical economically than previous vaccine recommendations. 25,53,54 In addition, a microsimulation model in which it was assumed that PCV13 efficacy in adults would be comparable to PCV7 in children, together with reasonable assumptions regarding risks and costs of IPD and non-bacteraemic pneumonia, projected that routine PCV13 in place of PPV23 would result in a greater reduction in burden of pneumococcal disease in US adults. 55 The question remains however, as to whether the success of the PCVs can be convincingly extrapolated to adults.…”
mentioning
confidence: 99%